Borocyclopropanation of Styrenes Mediated by UV‐light Under Continuous Flow Conditions. (12th September 2018) - Sayes, Morgane; Benoit, Guillaume; Charette, André B.
Abstract: Herein, we report a user‐friendly and metal‐free UV‐A light mediated borocyclopropanation of styrenes using continuous flow technology. A broad range of styrene derivatives can be cyclopropanated in good yields within 1 h residence time to produce highly valuable cyclopropylboronate esters with modest to good diastereoselectivities. The reaction is also applicable to α‐substituted styrenes. Mechanistic studies support a photoredox process during which xanthone, a well‐known organic photosensitizer, can easily reach a photoexcited state that is available for both an oxidative and a reductive quenching.